Bayesian and Fuzzy Approach to Assess and Predict the Maintainability of Software: A Comparative Study. (17th January 2012) - Jeet, Kawal; Dhir, Renu
Abstract : Quality has always been one of the major issues responsible for the success of software. Maintainability is one of the characteristics of software quality. A large number of techniques were developed for the assess and predication of this characteristic. Most of these techniques do not decompose it to an actual assessment level and thus fail to give a detailed account of the impact of specific criteria. These techniques thus constrain their use as the basis for analysis quantitatively. In this paper, we develop a system based on fuzzy inference approach to assess and predict maintainability in a quantitative manner. This system is an enhancement of Bayesian approach which is using activity-based quality model to deal with maintainability. We also compare the proposed fuzzy technique with an existing Bayesian approach to depict the improvement achieved due to the advantageous accuracy of fuzzy over crisp approach.